Dual-templated 3D nitrogen-enriched hierarchical porous carbon aerogels with interconnected carbon nanosheets from self-assembly natural biopolymer gel for supercapacitors. (1st September 2020) - Li, Panyu; Xie, Hongyang; Liu, Yali; Wang, Jie; Wang, Xuqian; Xie, Yi; Hu, Wanrong; Xie, Tonghui; Wang, Yabo; Zhang, Yongkui
Abstract: This work reports the design and fabrication of nitrogen-enriched hierarchical porous carbon aerogel (NPCA) with high supercapacitance performance derived from self-assembly natural biopolymer gel using a novel dual-template method. The as-obtained NPCA exhibited a honeycomb-like 3D network architecture composed of interconnected carbon nanosheets with hierarchical porous structure, large specific surface area (SSA, large to ∼1438 cm 3  g −1 ) and high content of N element (large to ∼6%). The 3D hierarchical porous structure was designed and tailored to enhance the electron/ion transport ability. NaCl was in favor of the enhancement of SSA/graphitization degree and the support of 3D architecture, while NaOH played an important role in the formation of micropores. The N dopants were introduced to provide the extra pseudocapacitance, which could improve the performance of energy storage. It was also found that the SSA, graphitization degree and N dopants were highly affected by pyrolysis temperature. Among the resultant samples, NPCA-650 displayed the highest specific capacitance (264.3 F g −1 at 0.5 A g −1 ) attributed to not only the developed pore structure but also the abundant active N dopants. The as-assembled symmetric supercapacitor exhibited a high energy density of 12.4 Wh kg −1 with excellent cycling stability. Overall, this work provides a novel approach for the fabrication of low-cost biomass-based energy storage materials and could be also helpful for the design and tailoring of the hierarchical porous carbon aerogel architecture. Graphical abstract: Image 1 Highlights: Nitrogen doped carbon aerogels were fabricated from self-assembly biopolymer gel. A novel dual-template method was used to form 3D hierarchical porous structure. The carbon aerogel exhibited a high specific surface area of 760–1438 cm 3  g −1 . N atoms were retained into carbon skeleton (∼5.5%) at high pyrolysis temperatures. The carbon aerogel displayed a good energy storage performance.